Performance do processo de coagulação/floculação no tratamento do efluente líquido gerado na galvanoplastia - Vaz, Luiz Gustavo de Lima (2009)
The process of electroplating effluents with high levels of heavy metals and large amounts of dissolved and suspended materials, resulting in high values of color and turbidity, respectively. Because of these characteristics, the effluent of electroplating industries require efficient processes to achieve the levels of concentration and physical and chemical parameters recommended by the environmental legislation. In this context we evaluated the efficiency of organic coagulants (seeds of Moringa oleifera Lam, chitosan, Tanfloc SG and Acquapol C1) and inorganic (aluminum sulfate and ferric chloride) in the first stage of wastewater treatment of electroplating through a planning saturated Plackett and Burman (PB12) followed by a central composite rotational design (DCCR). The following variables were studied: concentration (C), velocity of rapid mixing (VMR) and slow (VML) and time of rapid mix (TMR) and slow (TML), with 30 min of sedimentation, and the response variables analyzed for each coagulant: color, turbidity, settleable solids and COD. Among the agents coagulants/flocculants tested after the completion of PB12, the best combination of results for the removal of the studied parameters occurred with chitosan. The operating conditions were optimized by the statistical program: TMR of 100 rpm, TML of 20 rpm, VMR and VML of 6 and 30 min, respectively, concentration of 12.67 ppm and sedimentation time of 30 min. These conditions it is expected to remove 89.44% of color, 96.87% of turbidity and 35.81% of COD. Based on the results obtained chitosan presented a promising coagulant to the wastewater treatment of electroplating.